Frontiers in Sustainability - Frontiers Media (Frontiers Media, 2026)
Frontiers in Sustainability is an interdisciplinary journal focused on advancing and developing novel solutions and technologies to enable a sustainable future. The journal is included in Scopus and the DOAJ, among others.
Keywords: Sustentabilidad ambiental; Revistas depredadoras; Predatory journals